Social ventures and social entrepreneurs: factors for success - Almeida, David F. T. (2012)
This project aims to study the factors for the success or failure of social ventures. Factors that may affect social entrepreneurs who act on such organizations. Hence, and in a more practical way, it aims to reply to the challenge of Instituto de Empreendedorismo Social on identifying a set of some recommendations for social entrepreneurs starting a social venture. The main topics in literature, still divergent on the subject, are: context, network, innovation, metrics, leadership, ethics, funding and skills. In order to understand the role of these factors on the development of social entrepreneurship projects, four social projects and respective social entrepreneurs were selected, encompassing different realities and characteristics. The main conclusions are: Social entrepreneurs‟ characteristics vary much from case to case and are not limitative to one‟s actions. The course of a social project is highly shaped by their background and previous experiences. The more relevant factors contributing for the success are: project’s innovation, ethical behavior, relationship with society, network, leadership and local institutions were the most relevant ones. Some barriers to success were also detected, being the more impactful the lack of funding, perceived project’s image and lack of human resources. Metrics used to measure this success/failure are still in a baby stage and need to be developed further since are highly centered on project‟s activity, and not that much on its impact. Although findings point out the inexistence of a recipe on doing social entrepreneurship, common factors were identified in the studied cases, in spite of being very different situations. Then, although it is not possible to generalize the conclusions of four cases studies only, some recommendations for social entrepreneurs starting up a social venture may be formulated: a) Learn about social entrepreneurship concept; b) Value people; c) Manage volunteer hands wisely; d) Be ethical; e) Create commitment to the project; f) Give proper value to the network; g) Communicate effectively with society; h) Define well the sources of funding, and aim self-sustainability at least in the long-term; i) Define proper and useful metrics; j) Highlight complementarity; k) Be strong and resilient. Social ventures and social entrepreneurs: factors for success.